Problems of conceptual apparatus in environmental economics: relationship between the systems and mechanism of land use - Martyn, A.; Barvinsky, A.; Tykhenko, R. (Land Management, Cadastre and Land Monitoring, 2018)
The analysis of the relation between categories "system" and "mechanism" and their use in the economy of land use is given. It is shown that the ecological-economic mechanism is an important component of the land use system and the main tool for the realization of its functions. Key words: mechanism, system, land use economics, category, tool, terminology.